SAT0198 The Desscipher Project in Systemic Sclerosis (SSC): Observational Data on Digital Ulcers (DU) Prevention from The Eustar Group. (15th July 2016) - Blagojevic, J.; Abignano, G.; Allanore, Y.; Avouac, J.; Cometi, L.; Czirják, L.; Denton, C.; Distler, O.; Frerix, M.; Guiducci, S.; Huscher, D.; Jaeger, V.K.; et al.
Abstract : Background: In SSc, the management of DU is a problem in clinical practice, therefore their prevention is highly warranted. Sildenafil, iloprost, calcium channel blockers (CCB), ACE inhibitors (ACEi) and bosentan, alone or in combination, are used for DU prevention without unanimous agreement. Objectives: DeSScipher ("to decipher the optimal management of SSc") is an EC-funded FP7 research project that consists of five observational trials (OT) addressing different aspects of SSc. The aim of OT1 was to evaluate the efficacy of vasoactive and vasodilating drugs or a combination therapy for the management of DU in SSc. Methods: Longitudinal data were collected for up to 24 months by 28 DeSScipher centres. In SSc patients, the efficacy of sildenafil, bosentan, sildenafil+bosentan, iloprost or CCB /ACEi for the prevention of new DU was evaluated. Clinical features, ulcer type and other drugs were also recorded. Time without new DU, proportion of patients without new DU, risk of developing new DU and the mean number of new DU per patient were evaluated at 6 months follow-up. Results: In OT1, 1394 patients were enrolled. The history of DU was a significant risk factor for developing new DU (OR=3.146; (95%CI:1.19–8.31), p=0.021), therefore analysis was focused on secondary prevention (prevention of new DU in patients with DU history). 473/1394 (33.9%) had a history of DU and 268/473 (56.7%) had follow up data (58.2% limited and 41.8% diffuse SSc subset). 47/268 (17.5%) were on Bosentan, 33/268 (12.3%) on Sildenafil, 40/268 (14.9%) on Iloprost, 31/268 (11.6%) on Sildenafil and Bosentan combination and 117/268 (43.7%) on CCB/ACEi alone. In patients with history of DU in the last 24 weeks, the treatment with CCB/ACEi alone was associated with 7 fold increased risk of developing new DU compared to all other treatment arms (OR =7.313; 95%CI:1.248–42.85, p=0.027). Patients on concomitant immunosuppressive treatment had a trend towards faster DU recurrence. Conclusions: History of DU in the past 24 weeks should prompt a more aggressive preventive strategy other than therapy with CCB/ACEi alone due to its lower efficacy to prevent DU recurrence compared to the other treatment options. Acknowledgement: The DeSScipher project was funded by the European Community's Framework Programme 7 (FP7-HEALTH-2012.2.4.4–2 - Observational trials in rare diseases) under grant agreement N° 305495. We acknowledge the contribution of the following EUSTAR centers: Ancona (member N°34), Assiut (168), Bad Bramstedt (187), Belgrade (55), Bucharest (100), Cluj-Napoca (16), Erlangen (106), Frankfurt (124), Hamburg (64), Iasi (162), Istanbul (21), Istanbul (133), Köln (44), Monserrato (142), Moscow (78), Moscow (190), Padua (31), Rome (94), Salford/Manchester (80), Tübingen (56), Wuppertal (192). Disclosure of Interest: None declared